Difficulties and learning progress demonstrated by pedagogy students in a mathematics course (Research, Society and Development, 2022)
The article discusses learning difficulties and progress in applying the concept of divisibility in a course offered to undergraduate students and the pedagogical implications of its didactic exploration in primary school. During the diagnostic evaluation, the students showed little knowledge about the subject of knowledge (Euclid's algorithm), as well as when interpreting the obtained results, they also showed little knowledge in solving problems with an unknown term in the division algorithm. The diagnosis served as an indication that the low performance of the students might be due to a lack of knowledge of some mathematical concepts and served as a point of reference for (re)planning the course. This is a qualitative and interpretive research. During the development of the course, the students appropriated the concepts of divisibility and showed significant learning progress by the end. However, the research points to the need for teachers teaching mathematics in pedagogy courses to consider the possibility of applying different forms of Euclid's algorithm in a way that meets students' needs and contributes to their professional training. Considering that in this perspective the assessment of learning is consolidated through the process of analysis and critique of reality in order to transform it.